2020
DOI: 10.1101/2020.08.28.272336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PrkC modulates MreB filament density and cellular growth rate by monitoring cell wall precursors

Abstract: How bacteria link their rate of growth to the external nutrient conditions is not known. To explore how Bacillus subtilis modulates the rate cells expand their encapsulating cell wall, we compared the single-cell growth rate to the density of moving MreB filaments under different conditions. MreB filament density scales with the growth rate, and is modulated by the mur genes that create the cell wall precursor lipid II. Lipid II is sensed by the serine/threonine kinase PrkC, which, among other proteins, phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 35 publications
1
21
2
Order By: Relevance
“…A regulatory role of peptidoglycan insertion for autolytic activity is supported by previous studies suggesting that the two redundantly essential cell-wall hydrolases of B. subtilis, LytE and CwlO, are controlled by the three MreB homologs (Carballido-López et al, 2006;Domínguez-Cuevas et al, 2013). Furthermore, the amount of moving MreB filaments and cell-envelope growth are highly correlated across different growth conditions (Sun and Garner, 2020), which is compatible with a rate-limiting role of MreB-based cell-wall insertion. However, a molecular mechanism linking cell-wall insertion and cell-wall expansion has not been identified.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…A regulatory role of peptidoglycan insertion for autolytic activity is supported by previous studies suggesting that the two redundantly essential cell-wall hydrolases of B. subtilis, LytE and CwlO, are controlled by the three MreB homologs (Carballido-López et al, 2006;Domínguez-Cuevas et al, 2013). Furthermore, the amount of moving MreB filaments and cell-envelope growth are highly correlated across different growth conditions (Sun and Garner, 2020), which is compatible with a rate-limiting role of MreB-based cell-wall insertion. However, a molecular mechanism linking cell-wall insertion and cell-wall expansion has not been identified.…”
Section: Introductionsupporting
confidence: 53%
“…In visionary and influential work, Koch (1983) suggested that 'smart autolysins' are activated based on mechanical stress in the cell wall, which, in turn, is caused by turgor pressure. However, more recent works imply that the MreB-linked cell-wall insertion machinery provides the major regulator of cell elongation in B. subtilis (Daniel and Errington, 2003;Billaudeau et al, 2017;Domínguez-Cuevas et al, 2013;Rojas et al, 2017;Sun and Garner, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, we found that the B. subtilis septal constriction and overall cell growth rate are strongly coupled, with a linear dependence of septal constriction rate on cell growth rate. The molecular mechanism of coupling between septal constriction and cell growth rate requires further research, but possibilities include control of septal synthesis via overall levels of cell wall precursor 41,42 or levels of cell wall synthesis proteins, or direct regulation of cell wall synthesis protein activity via signalling 43 .…”
Section: Discussionmentioning
confidence: 99%
“…An interesting possibility of precursor availability driving the elongasome activity is suggested, based on the observed interaction of the MurG-MraY complex with MreB (106). Although there is a lack of further evidence for this observation in E. coli, a recent study in B. subtilis shows that MreB filament formation is regulated by RodZ in response to lipid-II abundance, resulting in growth rates that are proportional to nutrient availability (182).…”
Section: Elongation Synthesis: Scaffold Formation By Rod Complexmentioning
confidence: 99%
“…Depletion of elongasome components is lethal in rapidly growing cells due to loss of rod morphology; however, single-gene-deletion mutants are viable and grow poorly as small spheres in nutrient-limiting conditions (183). Interestingly, conditional lethality of mreBCD, rodZ, rodA, and pbp2 is suppressed by overexpression of FtsZ, an essential cytoskeletal factor initiating cell division, which can also be achieved by an increase in cellular concentration of ppGpp, a stationary-phase signaling molecule (164,(175)(176)(177)(178)(179)(180)(181)(182)(183). It is believed that upon inhibition of the elongasome, overexpressed FtsZ may push the cell cycle toward division, bypassing the need for elongation altogether.…”
Section: Elongation Synthesis: Scaffold Formation By Rod Complexmentioning
confidence: 99%